Contrasting physical and chemical conditions of two rock glacier springs. Issue 4 (29th April 2021) - Brighenti, Stefano; Engel, Michael; Tolotti, Monica; Bruno, Maria Cristina; Wharton, Geraldene; Comiti, Francesco; Tirler, Werner; Cerasino, Leonardo; Bertoldi, Walter
Abstract: Rock glaciers are increasingly influencing the hydrology and water chemistry of Alpine catchments. During three consecutive summers (2017–2019), we monitored by recording probes and fortnightly/monthly field campaigns the physical and chemical conditions of two rock glacier springs (ZRG, SRG) in the Zay and Solda/Sulden catchments (Eastern Italian Alps). The springs have contrasting hydrological conditions with ZRG emerging with evident ponding (pond‐like), and SRG being a typical high‐elevation seep (stream‐like). Water temperature was constantly low (mean 1.2°C, standard deviation 0.1°C) at both springs. Concentrations of major ions (dominated by SO4 2−, HCO3 −, Ca 2+ and Mg 2+ ) and trace elements (As, Sr, Ba, U, Rb) increased, and water became more enriched in heavy stable isotopes (δ 18 O, δ 2 H) towards autumn. This solute and isotopic enrichment had an asymptotic trend at SRG, and a unimodal pattern at ZRG, where peaks occurred 60–80 days after the snowmelt end. Wavelet analysis of electrical conductivity (EC) and water temperature records revealed daily cycles only at SRG, and significant weekly/biweekly fluctuations at both springs attributable to oscillations of meteorological conditions. Several rainfall events triggered a transient (0.5–2 h) EC drop (of 5–240 μS cm −1 ) and water temperature rise (of 0.2–1.4°C) at SRG (dilution and warming), whereas only intense rainfall events occasionally increased EC (by 15–85 μS cm −1 ) at ZRG (solute enrichment and thermal buffering), with a long‐lasting effect (6–48 h). Building on previous research, we suggest that rock glacier springs with differing flow conditions, that is, stream‐like and pond‐like, have contrasting fluctuations of water parameters at different timescales. Thus, for pond‐like springs, peaks of EC/solute concentrations might indicate a seasonal window of major permafrost thaw. Our quantitative description of the hydrochemical seasonality in rock glacier outflows and the physical and chemical response to precipitation events provides relevant information for water management in mountain areas under climate change. Abstract : We describe the distinct patterns of water temperature, turbidity, electrical conductivity, water stable isotopes and element concentrations of two different springs fed by active rock glaciers. Permafrost presence drives the common hydrochemical conditions, and the seasonal timing of permafrost thaw in rock glaciers can be revealed by distinct water proxies. Stream‐like and pond‐like springs have distinct trends of solute enrichment during the snow‐free season, and a contrasting hydrochemical response to rainfall events.